Pengaruh Pengunaan Model Problem Based Learning Terhadap Hasil Belajar Siswa Mata Pelajaran IPAS di SDK Waipanda Kelas IV - Doda, Fransiskus; Talo, Yohana Anggreni; Lende, Petrus (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effect of implementing the Problem-Based Learning (PBL) model on the learning outcomes of fourth-grade students at SDK Waipanda in Natural and Social Sciences (IPAS). The study used a quantitative approach with a pretest–posttest control group design. The sample consisted of 20 students selected purposively, namely 10 students in the experimental class and 10 students in the control class. The research instrument was an IPAS learning outcome test consisting of 15 multiple-choice questions that had been validated. Data collection was conducted through pretest and posttest, then analysed using normality test, homogeneity test, and t-test. The results showed that the average pretest score of students was 41.00 and increased to 56.75 on the posttest. The t-test confirmed a significant difference between learning outcomes before and after the implementation of the PBL model with a significance value of < 0.05. These findings indicate that the PBL model has a positive effect on the learning outcomes of Grade IV students in IPAS. Thus, it can be concluded that the implementation of Problem Based Learning can improve student learning outcomes and is suitable as an alternative in IPAS learning in primary schools.